Systemic therapy – A practical implementation of systemic thinking - Ludewig, Kurt (Kultura-Społeczeństwo-Edukacja, 2020)
A summary presentation of the historic development of systemic therapy as the follow-up to family therapies, with the usage of new metatheoretical thinking from the constructivist point of view is followed by a description of the material theoretical conditions of this psychotherapeutic approach, with particular consideration for the theories of cognition and autopoiesis by Chilean biologist Humberto Maturana as well as the sociological system theory according to German sociologist Niklas Luhmann. This is followed by an understanding of interaction systems with respect to the theory of therapy, as developed by the author – the member concept, as well as a system-theoretical adequate conceptualisation of psychical systems. The work ends with a short presentation of the implementation of the described theoretical concepts in systemic therapy practice.